Failed MitraClip therapy: surgical revision in high-risk patients - Mkalaluh, Sabreen; Szczechowicz, Marcin; Karck, Matthias; Weymann, Alexander (Journal of cardiothoracic surgery, 2019)
MitraClip implantation is a valid interventional option that offers acceptable short-term results. Surgery after failed MitraClip procedures remains challenging in high-risk patients. The data on these cases are limited by the small sample numbers.
Gesehen am 22.05.2019